Biomass Utilization of Spirulina platensis Powder in The Manufacture of Lozenges - Jeri Srinur Eka Saputra; Tri Winarni Agustini; Eko Nurcahya Dewi (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2014)
Many microalgae of the type S. Platensis are cultivated in Indonesia. Nutrient content owned by S. Platensis microalgae is very good for health, especially the protein content. Innovation diversification of the product is in the form of lozenges. This study aimed to examine the use of S. Platensis biomass powder into lozenges and know the quality of products made from added powder S. Platensis lozenges in physical, chemical, and sensory. The material used in this study were S. Platensis powder obtained from Sukoharjo. The method used in this study was experimental laboratories. The data tested in parametric is analyzed using T-test experimental design with three replications, whereas for non-parametric data is analyzed with Kruskal-Wallis and test continued with Multiple Comparison test. Analyzed data on physical parameters such as hardness and friability; chemicals such as moisture content, protein, and amino acid lysine; sensory (hedonic). The results showed that the formula KI (added S. Platensis powder 20 %) significantly (p<0,05) on physical parameters such as hardness and friability; chemicals such as moisture content, protein, and amino acid lysine; sensory (hedonic). Spirulina lozenges formula KI the physical quality of tablets: uniformity of weight (1.001 gram); hardness (4.893 Kp); friability (0.119 %); chemical: water content (2.285 %), protein (24.327 %); highest amino acid profile were L-Aspartic (14.026,3 ppm) and lowest amino acid profile was L-Isoleucine (846,37ppm) as well as the sensory hedonic with an average value of 7.080.Keyword: Lozenges, quality, Spirulina platensis powder